Nursing pay by gender distribution in the UK - does the Glass Escalator still exist?. (May 2019) - Punshon, Geoffrey; Maclaine, Katrina; Trevatt, Paul; Radford, Mark; Shanley, Oliver; Leary, Alison
Abstract: Aims and objectives/background: Nursing is a predominantly female profession. This is reflected in the demographic of nursing around the world. Some authors have noted that despite being a gendered profession men are still advantaged in terms of pay and opportunity. The aim of this study was to examine if the so called glass escalator in which men are advantaged in female professionals still exists. Design and method: Descriptive statistics of the routinely collected national workforce datasets from across the UK central repositories and mining of a bespoke data set that has been curated which focuses on the activity of specialist advanced practice clinical nurses. Results: Even in a gendered occupation such as nursing the advantage of men in terms of pay is apparent with men being over-represented at senior Bands compared to their overall proportion in the UK nursing population. From the bespoke dataset there also seem to be an advantage in term of faster attainment of higher grades from the point of registration. Conclusion and relevance to clinical practice: Reward and remuneration are essential to the workforce. This work reveals a gender differential towards men in higher paid nursing work. The drivers for this are complex and further work is required to determine the factors associated with career progression with men in nursing, and the rate limiting factors with the female workforce.